Radiographic Assessment of Post-Endodontic Pain - Sameer Hatem Abdul Haleem (Institute of Medico-legal Publications Pvt Ltd, 2021)
Aim:To radiographically assess and identify the factors that influence post-endodontic pain (PEP) in patientsreceived nonsurgical root canal treatment. Study Design: a longitudinal study. Place and Duration ofStudy: the study performed on 375 patients (200 male, 175 female), aged 15–65 years randomly attend Dr.Sameer Hatem private clinic in Karbala between 2014- 2019 Method. the complete history of patients wastaken, clinically examined and then radiographically examined by CSN x-ray machine and Xpod digitalsensor to identify the possible factors and assess the status of previously treated teeth, the patients dividedinto groups according to the age, causative factors, and the onset of pain from patients’ chief complain.Results:(Table.2) shows the differences in numbers and percentages of overall patients according to theonset and the causative factors of pain after root canal treatment, the high percentage of the pain of 102/(27.2%) of patients was due to overextension of filling material, (most of these patients were suffering fromspontaneous pain 47.05%). Followed by 78/(20.8%) which were due to failure of treatment due to underfilled root canal (most of them 34.61% have intermittent pain). Conclusion: Periapical x-ray radiographyis a valuable technique to identify the causative factors of post endodontic pain and evaluate the success ofRCT and the status of endo treated tooth and periapical tissues. All procedural errors can not be depicted onradiographs.